Robustness of corroded reinforced concrete structures: a structural performance approach - Cavaco, Eduardo (2013)
The aim of this work is to provide new contributions in order to define more accurately the structural robustness concept, particularly when it is applied to corroded reinforced concrete (RC) structures. To fulfill such task, several robustness indicators are analyzed and discussed with special emphasis given to the structural performance based measures. A new robustness definition and a framework to assess it are then proposed, based on the structural performance lost after damage occurrence. The competence of the proposed methodology is then tested comparing the robustness of two reinforced concrete foot bridges under corrosion. Damage considered is the longitudinal reinforcement corrosion level and load carrying capacity is the structural performance evaluated. In order to analyze corrosion effects, a finite element based two step analysis is adopted. On the first step a cross section analysis is performed to capture phenomenons such as: expansion of the reinforcement due to the corrosion products accumulation; damage and cracking in the reinforcement surrounding concrete; steel-concrete bond strength degradation; and effective reinforcement area reduction. The results obtained are then used to built a 2D structural model, in order to assess the maximum load carrying capacity of the corroded structure. For each foot bridge, robustness is finally assessed using the proposed methodology.